EFEKTIFITAS LEMBAR KEGIATAN SISWA BERBASIS PENDEKATAN (CTL) PADA MATERI TEOREMA PYTHAGORAS UNTUK SISWA SMP - Muhammad Zulfikar Ikhsanuddin Akbar; Euis Eti Rohaeti; Eka Senjayawati (Departement of Mathematics Education, 2019)
One way for students to get meaningful learning is to provide Student Worksheets (LKS) based on theapproach Contextual Teaching and Learning (CTL). The purpose of this study is to analyze the feasibility of Student Activity Sheets that have been made before actually being used during the learning process. The method in this study is descriptive qualitative, with a sample of 33 students in one of the West Bandung District Junior High Schools. The instruments prepared were Student Worksheets (LKS) based on theapproach Contextual Teaching and Learning (CTL), validation questionnaires for material experts, linguists, media experts, and student response questionnaires. The results of the study are questionnaire material expert validation by 75%, linguists by 72%, media experts at 84.25% and student questionnaire responses at 78.63%. It can be concluded that students are interested in working on LKS, and the teacher must be a facilitator so that students do not misinterpret the contents of the LKS. Student Worksheets (LKS) based on theapproach Contextual Teaching and Learning (CTL) can be used in mathematics learning because students will feel more meaningful learning